Polaron in a quasi 1D cylindrical quantum wire - Fai, L.C.; Teboul, V.; Monteil, A.; Maabou, S.; Nsangou, I. (Condensed Matter Physics, 2005)
Polaron states in a quasi 1D cylindrical quantum wire with a parabolic confinement potential are investigated applying the Feynman variational principle.
The effect of the wire radius on the polaron ground state energy level,
the mass and the Frohlich electron-phonon-coupling constant are obtained for the case of a quasi 1D cylindrical quantum wire. The effect of anisotropy
of the structure on the polaron ground state energy level and the mass are
also investigated.
It is observed that as the wire radius tends to zero, the polaron mass and
energy diverge logarithmically. The polaron mass and energy differ from the
canonical strong-coupling behavior by the Frohlich electron-phonon coupling constant and the radius of the quasi 1D cylindrical quantum wire that
are expressed through a logarithmic function. Moreover, it is observed that
the polaron energy and mass for strong coupling for the case of the quasi
1D cylindrical quantum wire are greater than those for bulk crystals. It is
also observed that the anisotropy of the structure considerably affects both
the polaron ground state energy level and the mass. It is found that as the
radius of the cylindrical wire reduces, the regimes of the weak and intermediate
coupling polaron shorten while the region of the strong coupling
polaron broadens and extends into those of the weak and intermediate
ones. За допомогою варіаційного принципу Фейнмана вивчаються стани
полярона в квазіодновимірному циліндричному квантовому дроті з
параболічним обмеженим потенціалом. Досліджується вплив радіуса дроту на енергетичний рівень основного стану полярона, масу і
електрон-фонон постійну зв’язку Фрьоліха. Також вивчається ефект
анізотропії структури на енергетичний рівень основного стану полярона і його масу. Виявлено, що якщо радіус дроту прямує до нуля,
маса і енергія полярона розбігаються логарифмічно. Маса і енергія
полярона відрізняються від канонічної поведінки сильного зв’язку
на електрон-фонон постійну зв’язку Фрьоліха і на радіус квазіодновимірного циліндричного квантового дроту, які виражаються через
логарифмічну функцію. Більше того, спостережено, що енергія та
маса полярона для випадку квазіодновимірного циліндричного квантового дроту є більшими, ніж для випадку об’ємних кристалів. Також
виявлено, що анізотропія структури сильно впливає на енергетичний
рівень основного стану полярона та його масу. Знайдено, що якщо
радіус циліндричного дроту зменшується, режими слабкого та середнього зв’язку полярона скорочуються, тоді як область сильного
зв’язку полярона розширюється. Отримано аналітичні вирази для
енергетичного рівня основного стану полярона і для його маси для
випадку сильного зв’язку поляронів.